2010
DOI: 10.1039/c0ob00424c
|View full text |Cite
|
Sign up to set email alerts
|

Straightforward synthesis of enantiopure (R)- and (S)-trifluoroalaninol

Abstract: Two efficient routes are reported for the synthesis of both enantiomers of trifluoroalaninol in enantiopure form. The first pathway involves a Strecker-type reaction performed from a chiral trifluoromethyloxazolidine (Fox). The second route, which is more direct, involves, as a key step, the reduction of chiral oxazolidines or imines derived from ethyl trifluoropyruvate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…According to our previously reported procedure, the CF 3 -oxazolidine 16 was obtained in a high yield (95%) as a 75:25 diastereomeric mixture by the condensation of the ethyl trifluoropyruvate with N -Boc-( R )-phenylglycinol in the presence of PPTS (Scheme ). We already reported that this oxazolidine proved to be a convenient building block for the synthesis of various enantiopure α-CF 3 -amino acids , and amino alcohols . In other respect, we consider herein this kind of oxazolidines as original stable proline surrogates.…”
Section: Resultsmentioning
confidence: 98%
“…According to our previously reported procedure, the CF 3 -oxazolidine 16 was obtained in a high yield (95%) as a 75:25 diastereomeric mixture by the condensation of the ethyl trifluoropyruvate with N -Boc-( R )-phenylglycinol in the presence of PPTS (Scheme ). We already reported that this oxazolidine proved to be a convenient building block for the synthesis of various enantiopure α-CF 3 -amino acids , and amino alcohols . In other respect, we consider herein this kind of oxazolidines as original stable proline surrogates.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, they can be used as chiral ligands and auxiliaries. [9] We have found that the reaction of sulfinyliminopyruvates (R)-4 or (S)-4 with borane dimethylsulfide complex, independently of a reagents ratio, leads to reduction of both C=N bond and ester function with the formation of N-substituted aminoalcohols (R,R)-7 or (S,S)-7, respectively (Scheme 4). 19 F NMR monitoring of the reaction reveals that when one equivalent of BH 3 ⋅Me 2 S is used, the reaction mixture contains only signals of product 7 and unreacted starting imine 4.…”
Section: Resultsmentioning
confidence: 99%
“…[8a,9] The stereochemical assignments in Scheme 4 were made by comparing specific rotation of (S)-and (R)-8 with those of the known compounds. [9] Aza-Henry reaction with nitromethane. Reaction of imines with nitromethane is widely used for the preparation of βnitroamines and respective diamines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations